"Reception of the School Poetry Text at the Middle School Level: A Methodological Pedagogical Approach." - soltane, safia; abbas, -abderraouf (El Omda in Linguistics and Discourse Analysis, 2026)
The study falls under pedagogical receiving poetic text, attempting to analyze, understand and clarify the influences and influences that each variable presents (reader, text, context) in the teaching of poetic text in the middle stage, which makes the study open to diverse and interactive areas that attract the teaching and nutrition of poetic text. They are: reading and receiving, text, language education, cognitive psychology and learner pedagogy.